Phytochemical, Antioxidant and Antimicrobial Activities of Hevea brasiliensis Leaves Extract - Kusumarn Noipha; Piyanuch Suwannarat; Supattra Prom-in; Titpawan Nakpheng (Bogor Agricultural University, Indonesia, 2024)
Belonging to the Euphorbiaceae family, the Para rubber tree is formally referred to as Hevea brasiliensis in scientific terms. It is commonly known as an important economic commodity in Thailand because the natural rubber primarily originates from the milky latex obtained from the tree. However, the available research on the phytochemicals found in different parts of the rubber tree and their biological effects is quite restricted. This study aimed to determine the phytochemical constituents, antioxidant and antibacterial activity studies on the crude dry leaf extracts of H. brasiliensis. The results indicated the presence of alkaloids, anthraquinones, cardiac glycosides, coumarin, flavonoids, saponin, steroids, tannins, and terpenoids. The total phenolic content was 63.95±4.31 mgGAE/g in the ethanolic leaf extract. The ethanolic extract displayed notable effectiveness in scavenging free radicals (71.2±0.17%) at 500 μg/ml concentration and antioxidant capacity (the lowest IC50 value 42.57±0.91 μg/ml). The ethanol extract of the leaf of H. brasiliensis showed inhibition zone on all of the selected bacteria (gram-positive; Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermidis, and gram-negative; Escherichia coli, Pseudomonas aeruginosa) at 200 mg/ml. In conclusion, the dried leaves of H. brasiliensis compose phytochemicals that exhibit antioxidant and antibacterial activities and possesses the potential to act as a reservoir of plant-derived antibiotics and natural antioxidants.